KUALITAS PELAYANAN BAGI PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT UMUM DAERAH TELUK KUANTAN - Nengsih, Rela Setia; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Regional Public Hospital ( RSUD ) of Teluk Kuantan is a type of class C Hospital. This hospital is one of the government agencies designated as providers of social security programs especially to improve the quality of health care at the Regional Public Hospital( RSUD ) Teluk Kuantan. However, there are still some problems in the health services provided by the Regional General Hospital of Teluk Kuantan to patients BPJS participants. This was revealed because there are many complaints from patients of BPJS participants not satisfied with the health services provided. As the limitations of existing drugs in the Hospital so that patients have to pay for healthcare BPJS participants to other pharmacies, doctors delay in providing services so that patients have to wait a long time, and still feel the injustice of their patients get the service. Based on this, the researchers is interested in examining how Quality of Service for Participants of Social Security Administrator (BPJS) in the Regional Public Hospital of Teluk Kuantan.The theory used in this research is the theory of service quality by Zeithaml et al with views through five service indicators, namely: (1). Tangible (2). Reliability(3).Responsiveness(4).Assurance(5).Empathy. This reserach aims to determine the quality of service and the factors that affect the Quality of Service for Participants of Social Security Administrator (BPJS) in the Regional Public Hospital of Teluk Kuantan. This reserach used a qualitative approach. Informants in this reserach is the Head of Service Regional General Hospital of Teluk Kuantan, BPJS service officer at the Regional General Hospital of Teluk Kuantan, doctors, nurses and patients BPJS participants.Quality of Service for Participants of Social Security Administrator (BPJS) in the Regional Public Hospital of Teluk Kuantanhave not been felt to the fullest. It is seen from the supply of medication to participants BPJS very limited, facilities and infrastructure are inadequate, as well as the schedule of services is not timely. While the factors that affect the quality of Service for Participants of Social Security Administrator (BPJS) in the Regional Public Hospital of Teluk Kuantan is a factor of funds and facilities and infrastructure.Keywords: Quality of Service, Participants of BPJS